Single Nucleotide Polymorphisms Associated With Gut Homeostasis Influence Risk and Age-at-Onset of Parkinson's Disease - Gorecki, Anastazja M.; Bakeberg, Megan C.; Theunissen, Frances; Kenna, Jade E.; Hoes, Madison E.; Pfaff, Abigail L.; Akkari, P. Anthony; Dunlop, Sarah A.; Kõks, Sulev; Mastaglia, Frank L.; Anderton, Ryan S. (Frontiers in Aging Neuroscience, 2020)
Research is increasingly focusing on gut inflammation as a contributor to Parkinson's disease (PD). Such gut inflammation is proposed to arise from a complex interaction between various genetic, environmental, and lifestyle factors, however these factors are under-characterized. This study investigated the association between PD and single-nucleotide polymorphisms (SNPs) in genes responsible for binding of bacterial metabolites and intestinal homeostasis, which have been implicated in intestinal infections or inflammatory bowel disease. A case-control analysis was performed utilizing the following cohorts: (i) patients from the Australian Parkinson's Disease Registry (APDR) (n = 212); (ii) a Caucasian subset of the Parkinson's Progression Markers Initiative (PPMI) cohort (n = 376); (iii) a combined control group (n = 404). The following SNPs were analyzed: PGLYRP2 rs892145, PGLYRP4 rs10888557, TLR1 rs4833095, TLR2 rs3804099, TLR4 rs7873784, CD14 rs2569190, MUC1 rs4072037, MUC2 rs11825977, CLDN2 rs12008279 and rs12014762, and CLDN4 rs8629. PD risk was significantly associated with PGLYRP4 rs10888557 genotype in both cohorts. PGLYRP2 rs892145 and TLR1 rs4833095 were also associated with disease risk in the APDR cohort, and TLR2 rs3804099 and MUC2 rs11825977 genotypes in the PPMI cohort. Interactive risk effects between PGLYRP2/PGLYRP4 and PGLYRP4/TLR2 were evident in the APDR and PPMI cohorts, respectively. In the APDR cohort, the PGLYRP4 GC genotype was significantly associated with age of symptom onset, independently of gender, toxin exposure or smoking status. This study demonstrates that genetic variation in the bacterial receptor PGLYRP4 may modulate risk and age-of-onset in idiopathic PD, while variants in PGLYRP2, TLR1/2, and MUC2 may also influence PD risk. Overall, this study provides evidence to support the role of dysregulated host-microbiome signaling and gut inflammation in PD, and further investigation of these SNPs and proteins may help identify people at risk of developing PD or increase understanding of early disease mechanisms.